ANALISIS PENERAPAN SISTEM REPORT CENTER DENGAN METODE TAM PADA KOPERASI DI YOGYAKARTA - Dwi Yuli Prasetyo; Kusrini Kusrini; Andi Sunyoto (Jurusan Teknik Informatika, 2012)
Department of Industry Trade and Cooperation (Disperindagkop) DIY Province is one government office in Yogyakarta province that houses all the existing UKM and cooperation in the province of Yogyakarta. In a cooperation effort to standardize the reporting system in the Province of DIY, DIY Disperindagkop do center on implementation of the system report that there are a few cooperation in DIY Province which aims to standardize the system of financial reporting by cooperation in the province of Yogyakarta-based information systems and technology, so it will beneficial for internally cooperation in making management decisions and assist in the coaching system Disperindagkop provincial and regency / city. The purpose of this study was to model the level of user acceptance of information systems and technology through the application of systems report center on a cooperation approach in Yogyakarta province with the Technology Acceptance Model (TAM) and then designed a recommendation to increase the level of acceptance of information systems and technologies. User acceptance levels were measured using a questionnaire and then tested for compliance with TAM using Structural Equation Model (SEM) using the program SPSS and AMOS applications. From the results of assessment and testing can be concluded that the level of user acceptance (cooperation) to the application of systems report center said to be good (agree). Based on the model generated, can re-proposed several steps to improve the level of acceptance of such systems center report.